Clinical efficacy of weight loss herbal intervention therapy and lifestyle modifications on obesity and its association with distinct gut microbiome: A randomized double-blind phase 2 study - Cao, Ming-Zhuo; Wei, Chun-Hua; Wen, Ming-Chun; Song, Ying; Srivastava, Kamal; Yang, Nan; Shi, Yan-Mei; Miao, Mingsan; Chung, Danna; Li, Xiu-Min (Frontiers in Endocrinology, 2023)
Goals To assess the efficacy and safety of Chinese Medicine Prescription “W-LHIT” in subjects with simple obesity, and to explore its potential mechanism of action. Methods Thirty-seven patients aged 18 to 60 from Wei-En hospital (Weifang City, Shandong, China), participated in a double blinded, placebo-controlled study. Subjects were randomly divided into 2 groups, 18 in treatment and 19 in placebo group. The treatment group took the “W-LHIT” capsules for two months, while the control group received placebo capsules. Both groups accepted healthy lifestyle education materials. After a 2-month treatment, the placebo group transferred to open-label treatment after unblinding. Results 72.22% participants in the treatment group lost more than 5% of their body weight, compared with 36.84% in the placebo group (p < 0.001). Body weight loss and body mass index reduction of the treatment group were also significantly higher than those of the placebo group (p < 0.05). These changes were accompanied by increased abundance of Akkermansia muciniphila and Enterococcus faecium, and decreased abundance of Proteobacteria in gut microbiota. Furthermore, the treatment group also showed improvement in obesity-related comorbidities such as hypertension and elevation of liver enzymes. No serious adverse reactions were found during the study period. Weight did not rebound at a follow-up visit 2 months after treatment. Conclusion W-LHIT significantly improved body weight and comorbid conditions without obvious adverse reaction or rebound weight gain. These effects were associated with increased abundance of probiotics in gut microbiota. W-LHIT may have a potential for treating obesity in conjunction with healthy lifestyle modifications.